Exploring the Scientific Connotation of Gypsum in Baihu Decoction Compatibility with Heat-clearing Effect Based on Phase Composition - Wang, Yunyun; Zhang, Zhengxian; Peng, Haotian; Zeng, Huahui; Wu, Xiangxiang (Chinese medicine and natural products, 2025)
This study aimed to study the effects of different crystalline states of Sheng Shigao (raw gypsum, RG) and its inorganic elements on the antipyretic efficacy of Baihu Decoction (BHT).RG samples calcined at different temperatures were prepared. The phase composition of RG and Duan Shigao (calcination of gypsum, CG) as well as the changes in phase composition before and after adding water to RG calcined at specific temperatures, were determined using X-ray diffraction (XRD). A fever model was established by subcutaneously injecting 20% yeast suspension (10 mL·kg−1) into the backs of rats. The effects of BHT containing RG in different crystalline states on rat body temperature were measured. Serum levels of IL-1β, IL-6, and hypothalamic prostaglandin E2 (PGE2) were detected using ELISA. Serum Ca2+ levels were measured using a microplate method. The content of trace elements in RG and CG and the corresponding freeze-dried BHT powder was determined using inductively coupled plasma mass spectrometry (ICP-MS). The complexation of representative inorganic elements with mangiferin, a major active component in BHT, was investigated using UV-Vis spectroscopy and fluorescence spectroscopy. A validation model was established using RAW264.7 mouse macrophages. Drug-containing serum of BHT with different inorganic elements was prepared, and the nitric oxide (NO) levels in the cell supernatant of different treatment groups were measured using the Griess method. The mRNA levels of IL-6, TNF-α, and PGE2 in each group were detected using qPCR (real-time fluorescent quantitative PCR).After calcination, the phase composition of RG changed, and the content of inorganic elements in RG, CG170 (RG calcined at 170 °C), and CG350 (RG calcined at 350 °C) showed similar trends. Compared with RG, the content of Ca, Sr, Al, and Na in CG changed significantly. Compared with BHT, the content of Ca, Sr, Si, and Na in CG changed significantly when incorporated into the formula. Intermolecular interactions confirmed strong binding between mangiferin and Cu2+ and Al3+. Cu2+ and Fe3+ exhibited fluorescence quenching effects on mangiferin solution, while Al3+ and Zn2+ showed strong fluorescence enhancement, with fluorescence intensity increasing by 120-fold and 30-fold, respectively. In vitro evaluation of synergistic anti-inflammatory effects confirmed that Ca, Fe, Cr, Al, and Si exhibited synergistic anti-inflammatory effects.The crystalline state of RG has little effect on its antipyretic properties, while Ca, Sr, Na, Fe, and Al are likely the key material bases influencing its efficacy.
Keywords: gypsum; Baihu Decoction; heat-clearing; compatibility of medicines; phase composition